DIMENSIONS AND STRATEGIES FOR ONLINE SUCCESS: VOICES FROM EXPERIENCED EDUCATORS - Schrum, Lynne; Hong, Sunjoo (Online Learning, 2002)
Online learning has become a popular method of education. Faculty members may know little about how to assist students in succeeding in a new learning environment, and students may be ill-prepared to tackle the new demands put upon them. Therefore, this research seeks to identify dimensions of successful online learners by examining primary screening documents and then mapping them to the literature base. Next, experienced online educators are asked to review the dimensions and to provide strategies that they use to ensure student success. Seven dimensions are identified and confirmed as significant, each dimension with slightly different importance— including access to tools; technology experience; learning preferences; study habits and skills; goals or purposes; lifestyle factors; and personal traits and characteristics. In addition, several online teaching strategies (including students’ posting biographies; frequent interaction; collaboration; requiring participation; question-asking forums; topical flexibility; and minimizing technology requirements) have been recommended.